2021
DOI: 10.3390/molecules26237116
|View full text |Cite
|
Sign up to set email alerts
|

Purification, Structural Characterization, and Anti-Inflammatory Effects of a Novel Polysaccharide Isolated from Orostachys fimbriata

Abstract: The present study elucidated the structural characteristics and anti-inflammatory activity of a novel polysaccharide isolated from Orostachys fimbriata, which is a traditional Chinese medicinal plant. O. fimbriata polysaccharide (OFP) was extracted and subsequently purified by chromatography using a DEAE cellulose-52 and Sephadex G-75 column. The molecular weight was determined as 6.2 kDa. HPGPC and monosaccharide composition analysis revealed a homogeneous polysaccharide containing only Glc. Chromatography an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…The literature has demonstrated the beneficial impact of glucans on inflammatory conditions (da Nascimento Santos et al, 2014; Li et al, 2017). Similar anti-inflammatory effects of 1, 4, 6-Glcp glycosidic bond have been reported previously (Hu et al, 2021). At present, polysaccharide activity is commonly believed to be greater in the β conformation.…”
Section: Resultssupporting
confidence: 90%
“…The literature has demonstrated the beneficial impact of glucans on inflammatory conditions (da Nascimento Santos et al, 2014; Li et al, 2017). Similar anti-inflammatory effects of 1, 4, 6-Glcp glycosidic bond have been reported previously (Hu et al, 2021). At present, polysaccharide activity is commonly believed to be greater in the β conformation.…”
Section: Resultssupporting
confidence: 90%
“…Previous studies have reported that saccharides, especially polysaccharides, from different plants played an important role in their anti-inflammatory properties. [25][26][27][28] However, their high molecular weight may negatively affect their beneficial effect, and for some polysaccharides, molecular degradation modification is required to enhance their activity by reducing their molecular weight to improve their bioavailability. 29 It is suggested that the natural oligosaccharides present in the plant have a lower molecular weight and greater solubility, foreshadowing that oligosaccharides may exhibit similar or even greater activity.…”
Section: Introductionmentioning
confidence: 99%
“…It contains many bioactive compounds such as organic acid, sugars, triterpenoids (glutinol, glutinone, friedelin, epi-friedelanol, β-amyrin, and taraxerone), triterpenes, phytosterols (β-sitosterol and campesterol), sterol glucosides, and flavonoids. Epicatechin gallate, quercetin, and kaempferol are known to be the major flavonoids found in the plant [ 13 , 14 ]. It is a widely used herb in various traditional medicine systems of China, Korea, and other Asian countries, and has been reported in various research articles for its promising biological activities [ 15 ].…”
Section: Introductionmentioning
confidence: 99%